Face scabies in the elderly: when dermoscopy can be a game changer (Dermatology Reports, 2024)
Dear Editor,Scabies is a common pruritic ectoparasitic infestation of the skin caused by the mite Sarcoptes scabiei. It classically presents as an intensely pruritic eruption that usually involves hands and interdigital folds, wrists, axillae, areolae, abdomen, and genitalia. In immunocompetent adults, mite infestation affecting the face is considered exceptional; accordingly, if topical treatment is chosen, clinicians typically instruct patients to apply the product to the body, excluding the head area. [...]